FACTORS INFLUENCING PARTICIPATION IN EARLY CHILDHOOD EDUCATION: ITS IMPLICATION TO QUALITY-EDUCATION - Gobena, Gemechu Abera (International Online Journal of Education and Teaching, 2020)
The study was investigated Factors Influencing Participation in Early Childhood Education: Its implication to quality-education. Descriptive survey research design was employed. Stratified random sampling techniques were used to collect pertinent information through questionnaire and observational checklists. The first finding was that 68.92% of the total variance of the factors contributed to quality of Early Childhood Education was site of the preprimary schools, lack of enough spaces for children practices, instructional materials kind & in amount, and availability of curriculum materials to each child in classroom. The second finding was that most teaching materials and curriculum contents (83%) were not from indigenous sources. Finally, large class sizes, high teacher-child ratio, low staff salaries, lack of well trained staff, poor relevance of curriculum, and lack of parental involvement were found to be the major influencing factors affecting early childhood’s quality-education. Therefore, policymakers should be clear with the aims of Early Childhood Education.